Technical Assistance in Improving the Capabilities of the Internal Audit Unit (SPI) of UIN Mataram Towards Good University Governance (GUG) - Hayati, Sirrul; Ceacilia Srimindarti (Society : Jurnal Pengabdian Masyarakat, 2025)
This service is dedicated to providing technical assistance aimed at enhancing the capabilities of the Internal Supervisory Unit (SPI) at UIN Mataram in order to promote Good University Governance (GUG). The primary concern is that the SPI has limited capabilities in executing its supervisory, risk management, and strategic consulting functions. As a result, the SPI is not fully optimizing its role in ensuring accountability, transparency, effectiveness, and efficiency in university governance. This service aims to provide technical assistance to improve the capacity of the Internal Audit Unit (SPI) of UIN Mataram in order to support the realization of Good University Governance (GUG). The objective of this community service program is to improve the understanding, skills, and institutional capacity of SPI through technical assistance, human resource development, and the establishment of operational standards.  The community service methodology involves a participatory approach consisting of the following stages: analyzing the SPI’s institutional needs, conducting interactive discussions and case studies, and performing monitoring and evaluation to assess improvements in capability. The results of the activity showed a significant increase in the internal auditors' understanding of risk management, improvement of the audit reporting mechanism, and institutional commitment to strengthening the role of SPI. This assistance also encouraged the growth of a culture of accountability and transparency within the university. Thus, this community service made a real contribution to strengthening the SPI of UIN Mataram towards becoming a competitive, credible, and highly integrity university